Challenging the secular state : the Islamization of law in modern Indonesia - Salim, Arskal (University of Hawaii Press, 2008)
"Challenging the Secular State examines Muslim efforts to incorporate shari'a (religious law) into modern Indonesia's legal system from the time of independence in 1945 to the present. The author argues that attempts to formally implement shari'a in Indonesia, the world's most populous Muslim state, have always been marked by tensions between the political aspirations of proponents and opponents of shari'a and by resistance from the national government. As a result, although pro-shari'a movements have made significant progress in recent years, shari'a remains tightly confined within Indonesia's secular legal system. The author first places developments in Indonesia within a broad historical and geographic context, offering a provocative analysis of the Ottoman empire's millet system and thoughtful comparisons of different approaches to pro-shari'a movements in other Muslim countries (Saudi Arabia, Iran, Pakistan). He then describes early aspirations for the formal implementation of shari'a in Indonesia in the context of modern understandings of religious law as conflicting with the idea of the nation-state."--Jacket